Simultaneous Observation of the Orientation and Activity of Surface-Immobilized Enzymes - Jasensky, Joshua (Langmuir : the ACS journal of surfaces and colloids, 2018)
Surface immobilized enzymes have been widely used in many applications such as biosensors, biochips, biofuel production, and biofuel cell construction. Many factors dictate how enzymes' structure, activity, and stability may change when immobilized, including surface functionalization, immobilization chemistry, nature of the solid support, and enzyme surface density. To better understand how immobilization affects enzyme structure and activity, we have developed a method to measure both surface-sensitive protein vibrational spectra and enzymatic activity simultaneously. To accomplish this, an optical/fluorescence microscope was incorporated into a sum frequency generation (SFG) spectrometer. Using β-glucosidase (β-Glu) as a model system, enzymes were covalently tethered to a self-assembled monolayer surface using cysteine-maleimide chemistry. Their orientations were determined by SFG spectroscopy, with a single native cysteine residue oriented toward the functionalized surface, and activity measured simultaneously using a fluorogenic substrate resorufin β-d-glucopyranoside, with a loss of activity of 53% as compared to comparable solution measurements. Measuring β-Glu activity and orientation simultaneously provides more accurate information for designing and further improving enzymatic activity of surface-bound enzymes